2022
DOI: 10.52973/rcfcv-e32108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the inclusion of Medicago sativa in feed chicken Cobb 500

Abstract: The present research was carried out at the Santa Ines farm of the Faculty of Agricultural Sciences (FCA) of the Universidad Técnica de Machala (UTMACH), in the Province of El Oro (Ecuador), which objective was to evaluate the effect of the inclusion of Medicago sativa meal (alfarina) in broiler chicken Cobb 500 feed on productive parameters, carcass and sensory analysis. Poultry biosecurity standards established for open house systems were applied, trying to maintain comfort and well-being for the birds; a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, Shirzadegan and Taheri (2017), showed that the inclusion of lucerne meal at a level of 30 g/kg improved the body weight gain, feed intake, and feed conversion ratio (FCR) in Ross 308 broiler chickens. However, Varzaru et al (2020) and Sańchez et al (2022) found that lucerne meal inclusion levels of as high as 50 g/kg in the diet of Hubbard broiler chickens and of 40 g/kg in that of Cobb 500 broiler chickens did not affect either group's feed intake, daily weight gain, or FCR. The inclusion of dietary lucerne meal at a level ranging from 50 g/kg to 200 g/kg resulted in poor production performance (Tkaćǒváet al, 2011).…”
Section: Lucerne In Broiler Chicken Dietsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, Shirzadegan and Taheri (2017), showed that the inclusion of lucerne meal at a level of 30 g/kg improved the body weight gain, feed intake, and feed conversion ratio (FCR) in Ross 308 broiler chickens. However, Varzaru et al (2020) and Sańchez et al (2022) found that lucerne meal inclusion levels of as high as 50 g/kg in the diet of Hubbard broiler chickens and of 40 g/kg in that of Cobb 500 broiler chickens did not affect either group's feed intake, daily weight gain, or FCR. The inclusion of dietary lucerne meal at a level ranging from 50 g/kg to 200 g/kg resulted in poor production performance (Tkaćǒváet al, 2011).…”
Section: Lucerne In Broiler Chicken Dietsmentioning
confidence: 93%
“…The carcass traits of broiler chickens were also affected by the dietary inclusion of lucerne meal (Varzaru et al, 2020). Low inclusion levels (30 g/kg lucerne) improved the carcass weight, breast weight, and thigh weight (Shirzadegan and Taheri, 2017) of chickens, while higher levels (of 40 g/kg to 100 g/kg) dietary lucerne meal negatively affected these traits (Shirzadegan and Taheri, 2017;Paredes and Risso, 2020;Varzaru et al, 2020;Sańchez et al, 2022). This might be due to lowered feed intake, with higher dietary lucerne meal content resulting in the lowered body weight of chickens (Paredes and Risso, 2020).…”
Section: Saponin µG/g Dmmentioning
confidence: 99%
“…For the management of the B, the methodology described by Sánchez et al [17] was adapted to maintain 200 B of the Cobb 500 line. In order to generate the adequate comfort temperature, 4 JACKWALL gas brooders of 1,200 kilocalories• hours -1 (kcal•h -1 ) -4,700 British Thermal Unit•h -1 reference G14818 (Quito-Ecuador) were used as a source of heat and for the lighting program, 20-watt Light Emitting Diode (LED) bulbs were used, applying 24 h of light the first 7 days (d) and from then onwards subtracting 1 h per d until reaching only 6 h of artificial light.…”
Section: Characteristics Of the Housing And Management Of The Broilersmentioning
confidence: 99%